2012
DOI: 10.1371/journal.pone.0037073
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Inhibits L-Type Calcium Currents Depending upon the Protein Sulfhydryl State in Rat Cardiomyocytes

Abstract: Hydrogen sulfide (H2S) is a novel gasotransmitter that inhibits L-type calcium currents (I Ca, L). However, the underlying molecular mechanisms are unclear. In particular, the targeting site in the L-type calcium channel where H2S functions remains unknown. The study was designed to investigate if the sulfhydryl group could be the possible targeting site in the L-type calcium channel in rat cardiomyocytes. Cardiac function was measured in isolated perfused rat hearts. The L-type calcium currents were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 21 publications
4
59
0
1
Order By: Relevance
“…On the other hand, no significant differences were detected between NaHS-insensitive cells treated or untreated with Nifedipine (Fig. 2A) in agreement with an earlier report [23]. In particular, our data suggest that H 2 S-sensitive L-type VOCCs are active in resting conditions in a subpopulation of H9c2 cells.…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, no significant differences were detected between NaHS-insensitive cells treated or untreated with Nifedipine (Fig. 2A) in agreement with an earlier report [23]. In particular, our data suggest that H 2 S-sensitive L-type VOCCs are active in resting conditions in a subpopulation of H9c2 cells.…”
Section: Resultssupporting
confidence: 93%
“…More specifically, NaHS (up to 1 mM) causes a dose-dependent reduction in the Ca 2+ current peak. This effect is only partial: the current density diminishes by 50% at 1 mM NaHS [34]. The mechanism could involve a direct modification of Cav free sulfhydryl groups [34].…”
Section: Calcium Vocsmentioning
confidence: 98%
“…Indeed, whole patch clamp experiments in rat cardiomyocytes revealed that NaHS negatively modulates L-type Ca 2+ channels composed by the CaV1.2 subunits [12,30,34]. More specifically, NaHS (up to 1 mM) causes a dose-dependent reduction in the Ca 2+ current peak.…”
Section: Calcium Vocsmentioning
confidence: 99%
“…2,3) Some mechanisms have been proposed by which H2S exerts cardioprotective effects, including reduction of apoptosis, preservation of mitochondrial function, anti-inflammatory responses, and angiogenic actions. [4][5][6][7] However, the specific mechanism of cardioprotection mediated by H 2 S in I/R injury is still largely unknown.…”
Section: Hydrogen Sulfide a Potential Cardioprotective Gas Activatinmentioning
confidence: 99%